2017
DOI: 10.1016/j.jcbs.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of experiential avoidance in the relation between anxiety disorder diagnoses and future physical health symptoms in a community sample of young adult women

Abstract: Individuals diagnosed with an anxiety disorder report more physical health problems than those without an anxiety disorder. Few studies have examined the relation of anxiety disorders to later physical health symptoms, or the processes that may explain this relation. One process of interest is experiential avoidance (EA), which is commonly reported in populations characterized by high anxiety and often leads to health-compromising behaviors. The present study examined the relations between anxiety disorder dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 71 publications
1
14
0
1
Order By: Relevance
“…The present study first examined the association between social phobia symptoms and self‐reported physical symptoms among healthy undergraduate students. The findings showed that individuals with higher levels of social phobia symptoms reported more severe and frequent physical symptoms, which is consistent with previous findings obtained in clinical anxiety disorder samples (Berghoff et al, ; Kariuki‐Nyuthe & Stein, ; Kingery, Ginsburg, & Alfano, ; Kroenke et al, ; Niles et al, ). This finding provides evidence that social phobia symptoms are closely associated with self‐reported physical symptoms, suggesting that individuals with high social phobia symptoms might have more physical health problems.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study first examined the association between social phobia symptoms and self‐reported physical symptoms among healthy undergraduate students. The findings showed that individuals with higher levels of social phobia symptoms reported more severe and frequent physical symptoms, which is consistent with previous findings obtained in clinical anxiety disorder samples (Berghoff et al, ; Kariuki‐Nyuthe & Stein, ; Kingery, Ginsburg, & Alfano, ; Kroenke et al, ; Niles et al, ). This finding provides evidence that social phobia symptoms are closely associated with self‐reported physical symptoms, suggesting that individuals with high social phobia symptoms might have more physical health problems.…”
Section: Discussionsupporting
confidence: 90%
“…This scale is widely used to assess the experience of physical symptoms in different populations (e.g., Smolderen, Vingerhoets, Croon, & Denollet, ; Stevenson & Williams, ; Williams, Abbott, & Kerr, ). A recent study showed that the mean score on CHIPS of women with anxiety diagnosis was 30.18 ( SD = 25.60) and that of women without anxiety diagnosis was 14.56 ( SD = 15.47; Berghoff et al, ). In the present study, the mean score on CHIPS of participants with social phobia scores above cut‐off was 20.72 ( SD = 16.53) and that of participants with social phobia scores below cut‐off was 14.47 ( SD = 13.91).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The presence of such stressors promotes psychophysiological responses which can affect their health 30. In spite of the importance of research related to anxiety, there are few studies analysing the nature and strength of the relationship between anxiety and physical health problems in adulthood 31. Some of the most intense physical symptoms associated with anxiety are respiratory and stomach problems, cardiac alterations, migraine, menstrual pain, thyroid and psoriasis 32–35.…”
Section: Introductionmentioning
confidence: 99%